Incidence and risk factors of bacterial sepsis and invasive fungal infection in neonates and infants requiring major surgery: an Italian multicentre prospective study. (December 2022) - Auriti, C.; De Rose, D.U.; Santisi, A.; Martini, L.; Ronchetti, M.P.; Ravà, L.; Antenucci, V.; Bernaschi, P.; Serafini, L.; Catarzi, S.; Fiorini, P.; Betta, P.; et al.
Summary: Background: Limited data are currently available on the incidence rates and risk factors for bacterial sepsis and invasive fungal infections (IFIs) among neonates and infants undergoing major surgery. Aim: To assess the incidence of bacterial sepsis and IFI, fungal colonization, risk factors for sepsis, and mortality in neonates and infants aged <3 months undergoing major surgery. Methods: A multicentre prospective study was conducted involving 13 level-3 neonatal intensive care units in Italy, enrolling all infants aged ≤3 months undergoing major surgery. Findings: From 2018 to 2021, 541 patients were enrolled. During hospitalization, 248 patients had a bacterial infection, and 23 patients had a fungal infection. Eighty-four patients were colonized by fungal strains. Overall, in-hospital mortality was 2.8%, but this was higher in infected than in uninfected infants ( P = 0.034). In multivariate analysis, antibiotic exposure before surgery, ultrasound-guided or surgical placement of vascular catheters, vascular catheterization duration, and gestational age ≤28 weeks were all associated with bacterial sepsis. The risk of IFI was markedly higher in colonized infants (odds ratio (OR): 8.20; P < 0.001) and was linearly associated with the duration of vascular catheterization. Fungal colonization in infants with abdominal surgery increased the probability of IFI 11-fold (OR: 11.1; P < 0.001). Conclusion: Preventive strategies such as early removal of vascular catheters and the fluconazole prophylaxis should be considered to prevent bacterial and fungal sepsis in infants undergoing abdominal surgery, and even more so in those with fungal colonization.